How Firms Use Corporate Bond Markets under Financial Globalization - Gozzi, Juan Carlos (Elsevier, 2015)
This paper studies how firms from developed and developing countries have used domestic and international corporate bond markets since the 1990s. We find that debt issues in domestic and international markets have different characteristics. International issues tend to be larger, of shorter maturity, denominated in foreign currency, include more fixed rate contracts, and entail lower yields. These patterns persist even when analyzing issues by firms from countries with more developed domestic markets and higher financial integration and when comparing issues conducted by the same firm in different markets. These findings are consistent with the existence of frictions that segment domestic and international corporate bond markets and with these markets providing distinct financial services.